2015
DOI: 10.1634/theoncologist.2015-0050
|View full text |Cite
|
Sign up to set email alerts
|

Confronting Therapeutic Failure: A Conversation Guide

Abstract: We reflect on the impact of bad news on both clinician and patient in the setting of cancer treatment failure. We review the classic six-step SPIKES (setting, perception, invitation for information, knowledge, empathy, summarize and strategize) protocol for giving bad news that has been widely adopted since it was first published in this journal in 2005. The goal of such a conversation guide is to describe both the process and the tasks that constitute vital steps for clinicians and to comment on the emotional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 40 publications
(59 reference statements)
0
17
0
1
Order By: Relevance
“…However, it has been identified that these strategies lack robust supporting evidence (Fallowfield and Jenkins, 2004). This article will focus on the SPIKES protocol developed by Baile et al (2000) due to the frequency to which it is referred to in guidance (National Council for Hospice and Palliative Care Services, 2003, RCN, 2013, Seifart et al, 2014, utilised in teaching programmes (Baer et al, 2008) and adopted by clinicians (Morgans and Schapira, 2015). The evidence base for this approach will be examined and the utility and ethos of step-wise protocols will be discussed with the intention of providing a fresh perspective on breaking bad news.…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been identified that these strategies lack robust supporting evidence (Fallowfield and Jenkins, 2004). This article will focus on the SPIKES protocol developed by Baile et al (2000) due to the frequency to which it is referred to in guidance (National Council for Hospice and Palliative Care Services, 2003, RCN, 2013, Seifart et al, 2014, utilised in teaching programmes (Baer et al, 2008) and adopted by clinicians (Morgans and Schapira, 2015). The evidence base for this approach will be examined and the utility and ethos of step-wise protocols will be discussed with the intention of providing a fresh perspective on breaking bad news.…”
Section: Introductionmentioning
confidence: 99%
“…I was exceptionally pleased to read Morgans and Schapira's [1] paper, "Confronting Therapeutic Failure: A Conversation Guide," in The Oncologist.…”
mentioning
confidence: 99%
“…In essence, although this research examined grief in response to patient loss, the subtext of these studies is looking at relationships and attachments to patients. To my knowledge, Morgans and Schapira [1] are some of the few clinicians to openly acknowledge the issue of attachment in the context of patient communication.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Artigo recente (Morgans & Schapira, 2015) Cabe aqui destacar que os protocolos de comunicação cumprem uma função de orientar e divulgar informações sobre o manejo da comunicação em saúde para profissionais que precisam lidar com esta tarefa diariamente e nem sempre receberam treinamento adequado para tal. Eles se propõem sintetizar conhecimentos advindos de pesquisas diversas e apresentá-los de maneira estruturada, didática e em linguagem protocolar própria dos meios biomédicos (Baile et al, 2000).…”
Section: Importância E Dificuldades Da Comunicação Nos Cuidados Paliaunclassified